1740 S.C. Acts, An Act for the Better Ordering and Governing of Negroes and other Slaves in this Province, § 23 - (:unkn) unknown (My University, 1740)
Prohibited any "negro or slave" from possessing or using firearms or weapons without a ticket or license from their master, punishable by seizure of weapons.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES